Inhibition of nitric oxide synthesis ameliorates burn-induced remote organ injury in rats: A light microscopic study - (:unkn) unknown (My University, 2002)
Objective: To investigate the role of endogenous nitric oxide (NO) on remote organ injury in the early phase of burn trauma. Methods: Wistar albino rats (200-300 g) were exposed to 90°C (burn) or 25°C (sham) water bath for 10 sec. Results: Microscopic score in the stomach was increased in the burn group compared to sham. Hemorrhage areas, epithelial desquamation and glandular cell degeneration were observed in the gastric mucosa of the burn group. NG-nitro-Larginine methyl ester (L-NAME) treatment reduced the burn-induced damage score with an intact glandular architecture. In NG-nitro-Darginine methyl ester (D-NAME) pretreated groups, histologic scores were not different than burn group, with desquamated and degenerated surface epithelium. L-arginine (L-arg) plus LNAME pretreatment partially reversed this effect with prominent gastric mucosal damage. In the liver, the microscopic score was increased in the burn group compared to sham. Hepatocyte vacuolar degeneration, sinusoidal congestion and increased number of Kupffer cells were observed in the burn group. Hepatic injury was slightly attenuated by L-NAME treatment whereas D-NAME or L-arg plus L-NAME pretreatment was ineffective. Conclusion: In conclusion, inhibition of NO synthesis ameliorates gastric and hepatic damage, emphasizing the critical role of NO in the burn-induced remote organ injury.
Keywords: Burns; Myeloperoxidase activity; Nitric oxide; Remote organ injury